Improving the Corporate Governance System with the Application of Digital Transformations Necessary to Support the Management Decision-Making Process in the Company - Wenjuan Zhang; Anna Korenevskaya (Communications of International Proceedings, 2021)
The perspectives of companies for the future can be determined by key quality indicators. One of which is corporate governance. It is effective corporate governance that increases the investment attractiveness of a company and, thus, increases investment activity both in the company itself and in the country as a whole. The relevance of studying the problems of the effectiveness of corporate governance models in a corporation is due to an increase in its competitiveness and investment attractiveness in the national and international markets. Today, in the context of the global economic crisis caused by the pandemic, the relevance of studying the improvement of the corporate governance system is associated with the problem of economic instability in the world, a decrease in foreign investment in the country and a decrease in investor confidence. The effectiveness of corporate governance of a corporation affects the flow of foreign investment into the Chinese economy. Thus, the more efficient the corporate governance of the corporation, the higher the investment potential of the state.
Keywords: Digital Transformation; Corporate Governance; Corporation; Control; Shareholders; Pandemic; Competitiveness.